Aspects of iron metabolism - factors affecting iron absorption - Bezwoda, Werner, Robert (My University, 1983)
The investigations which make up the body of this thesis touch on various aspects of iron absorption. Although many of the factors governing iron absorption have been elucidated specific problems remain to be defined in greater detail. The aim of these investigations was therefore to define more fully some of the quantitative and qualitative aspects of dietary iron absorption
A thesis submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy.
Keywords: Iron; Metabolism; Absorption